Family Environment, Local History Pedagogy, and Cultural ‎Value Internalization: Associations with Heritage ‎Preservation Attitudes in Parepare, Indonesia - Jumaisa; Fawziah Zahrawati B; Besse Faradiba (Yayasan Darussalam Bengkulu, 2026)
This study examined the associations of local history pedagogy (X1), cultural value internalization (X2), and family environment (M) with senior high school students’ heritage preservation attitudes (Y), and tested whether the family environment moderated the two school-related associations. A cross-sectional quantitative design employed partial least squares structural equation modeling (PLS-SEM) in SmartPLS 4. Participants were 101 Grade XII students (75.4% response rate) purposively recruited from five public senior high schools in Parepare City, South Sulawesi, Indonesia. The measurement model showed acceptable indicator reliability, convergent validity, and internal consistency; however, discriminant validity was weak, particularly between X1 and X2, and the interaction terms exhibited severe collinearity. The structural model explained 54.4% of the variance in heritage preservation attitudes (R² = 0.544). Family environment showed the strongest direct association (β = 0.433, p < .001), followed by cultural value internalization (β = 0.357, p = .013), whereas local history pedagogy was not significant (β = 0.030, p = .839). Both interaction effects were non-significant. Given the cross-sectional design, modest sample, restricted variance, measurement overlap, and low power for interactions, the null effects should be regarded as inconclusive. The findings identify family environment as a salient correlate of heritage preservation attitudes but do not establish causal or generalizable relationships.